1996
DOI: 10.1104/pp.111.2.541
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Expression of the Tobacco Mosaic Virus Movement Protein in Transgenic Potato Plants Alters Plasmodesmal Function and Carbohydrate Partitioning

Abstract: ) were employed t o further explore the mode by which this viral protein interacts with cellular metabolism t o change carbohydrate allocation. Dye-coupling experiments established that expression of the TMV-MP alters plasmodesmal function in both potato leaves and tubers when expressed in the respective tissues. However, whereas the sizeexclusion limit of mesophyll plasmodesmata was increased to a value greater than 9.4 kD, this size limit was smaller for plasmodesmata interconnecting tuber parenchyma cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
62
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 21 publications
6
62
0
1
Order By: Relevance
“…These changes include (1) variation in chlorophyll fluorescence and reduced chlorophyll content [3], (2) inhibition of photosynthetic activity [17], (3) disproportionate accumulation of photoassimilates [1,23], (4) alterations in chloroplast ultrastructure and functions [4,25], (5) downregulation of nuclear-encoded chloroplast and photosynthesis-related genes and proteins (CPRGs and CPRPs, respectively) [8,21,34,35], (6) direct binding of viral components with chloroplast factors [4,33], and (7) perturbation of photosynthesis by regulation of host miRNA expression [43].…”
Section: Introductionmentioning
confidence: 99%
“…These changes include (1) variation in chlorophyll fluorescence and reduced chlorophyll content [3], (2) inhibition of photosynthetic activity [17], (3) disproportionate accumulation of photoassimilates [1,23], (4) alterations in chloroplast ultrastructure and functions [4,25], (5) downregulation of nuclear-encoded chloroplast and photosynthesis-related genes and proteins (CPRGs and CPRPs, respectively) [8,21,34,35], (6) direct binding of viral components with chloroplast factors [4,33], and (7) perturbation of photosynthesis by regulation of host miRNA expression [43].…”
Section: Introductionmentioning
confidence: 99%
“…Tuberization of potato stolons also is associated with a plasmodesmata transition that permits symplasmic unloading of carbon compounds as a result of the creation of plasmodesmata continuity between the phloem and the newly formed storage parenchyma of the tuber (Viola et al, 2001). Furthermore, modification of plasmodesmata permeability by expressing a viral MP leads to a modification in carbon partitioning in tobacco (Olesinski et al, 1995;Hofius et al, 2001) and potato (Olesinski et al, 1996;Almon et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to an increase in the size exclusion limit of plasmodesmata (Wolf et al, 1989), carbohydrate metabolism and partitioning was found to be altered in MP30 expressing plants Lucas et aL, 1996;Olesinski et aL, 1996). Levels of sucrose, glucose, fructose and starch were elevated in source leaves of transgenic tobacco plants, total biomass production was largely unaltered but the shoot to root ratio was changed in favour of shoots.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that in transgenic potato and tobacco plants plasmodesmata act as control site for carbohydrate translocation. The metabolic differences between both species have been suggested to derive from the use of different promoters or may be owing to different plasmodesmal constitutions allowing control by TMV-MP in various ways Olesinski et al, 1996).…”
Section: Introductionmentioning
confidence: 99%